A polyethylene isolation film with high residual bonding rate and preparation method thereof
By oxidizing titanium tetrachloride and compounding with graphene oxide nanosheets, a modified composite powder is formed and high-density polyethylene is modified, which solves the poor performance of the polyethylene isolation film under ultraviolet light conditions, and achieves good high temperature resistance, mechanical and ultraviolet resistance.
Patent Information
- Application Number
- CN202510275687.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-10
AI Technical Summary
Polyethylene isolation films have poor performance under ultraviolet light conditions, which are prone to aging and layer separation.
By anchoring the titanium tetrachloride on the surface of the silica carrier and oxidizing it into titanium dioxide, and compounding it with graphene oxide nanosheets, a modified composite powder is formed, and high-density polyethylene is modified to improve the heat resistance, mechanical properties and residual adhesion of the isolation film.
The high temperature resistance, mechanical properties and ultraviolet resistance of the polyethylene isolation film are significantly improved, and the silicon desilencing rate is reduced, and the performance is better than that of the solvent-coated isolation film.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of isolation films, and in particular relates to a polyethylene isolation film with a high residual bonding rate and a preparation method thereof. Background Art
[0002] Polyethylene, as a fully saturated hydrocarbon skeleton, is one of the most important commercial polymers and is widely used as a key component of pipes, plates, containers, films, cables, coatings, fibers and other necessities. The polyethylene isolation film material is soft, has high elongation, is flat and beautiful, has a high dry silicon content, has a low risk of being difficult to peel off, is recyclable, and is green and environmentally friendly. However, it has poor high temperature resistance and poor light resistance in outdoor lighting environments. It is prone to aging and yellowing, which causes the isolation film matrix polyethylene to separate from the aqueous silicone oil layer.
[0003] The Chinese invention patent application with publication number CN117325530A discloses a heat-resistant, low-desiliconization composite polyethylene isolation film and a preparation method thereof. The method comprises coating silicone glue on the original polyethylene film, adopting silicone coating cross-linking, and adopting a three-layer co-extrusion blow molding method, thereby improving the surface strength of the film and the thermal shrinkage performance of the material. However, the degree of improvement in the heat resistance of the original polyethylene isolation film in this scheme is low, and aging is prone to occur under ultraviolet light conditions.
[0004] A Chinese invention patent application with publication number CN117510916A discloses a method for preparing a high-temperature resistant modified polyethylene isolation film, in which a polyethylene isolation film with flame retardant and high-temperature resistant properties is prepared by mixing a modified polyamide obtained by condensation polymerization of m-phenylenediamine, isophthaloyl chloride and phosphorus-containing m-phenylenediamine with a modified polyethylene modified by vinyl nano-silica, maleic anhydride and diisopropylbenzene peroxide; however, this solution focuses on improving the flame retardant properties, and has little effect on improving the ultraviolet light resistance of the polyethylene isolation film. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of how to improve the performance of a polyethylene isolation film under ultraviolet light conditions, and to provide a polyethylene isolation film with a high residual bonding rate and a preparation method thereof.
[0006] The present invention anchors titanium tetrachloride on the surface of a silicon dioxide carrier and oxidizes it into titanium dioxide, and composites it with graphene oxide nanosheets to form a modified composite powder. The modified composite powder is used to modify high-density polyethylene to improve the heat resistance, mechanical properties and residual bonding rate of the polyethylene isolation film.
[0007] The purpose of the present invention can be achieved through the following technical solutions: A polyethylene isolation film with a high residual bonding rate comprises a surface layer, an intermediate layer, a bottom layer and a coating layer. The surface layer formula comprises the following raw material components by weight: 65-75 parts of modified high-density polyethylene, 5-8 parts of linear low-density polyethylene and 20-25 parts of maleic anhydride grafted polyethylene.
[0008] The middle layer formula contains the following raw material components: 65-75 parts of modified high-density polyethylene, 10-12 parts of filler masterbatch and 2-3 parts of color masterbatch.
[0009] The bottom layer formula contains the following raw material components: 65-75 parts of modified high-density polyethylene, 5-8 parts of linear low-density polyethylene and 10-12 parts of filler masterbatch.
[0010] Further, the modified high-density polyethylene is prepared by the following steps: Step 1: Disperse the loaded titanium composite powder in n-decane in a reactor, dissolve benzyl alcohol in benzene, add the mixture into the reactor, reflux at 35-45°C for 4-5h, remove the benzene solvent by rotary evaporation, reflux at 170-180°C for 8-9h, collect the precipitate by centrifugation, wash and vacuum dry to obtain the titanium oxide loaded composite powder.
[0011] Step 2: In a reaction kettle, the titanium oxide-loaded composite powder is modified with KH550 in ethanol to obtain a modified composite powder, and the modified composite powder is mixed with high-density polyethylene in a twin-screw extruder at 180-190° C. and 50-60 rpm for 10-12 minutes to obtain a modified high-density polyethylene.
[0012] Furthermore, the coating layer formula comprises the following raw material components by weight: 90-92 parts of silicone oil, 4-5 parts of cross-linking agent, 5-6 parts of curing agent and 0.3-0.4 parts of catalyst.
[0013] Furthermore, the crosslinking agent is hydrogen-containing siloxane, the curing agent is epoxy silane, and the catalyst is siloxane platinum complex.
[0014] Furthermore, in step 1, the usage ratio of the loaded titanium composite powder, n-decane, benzyl alcohol and benzene is 30-40 g: 300-400 mL: 6-8 mL: 35-40 mL.
[0015] Furthermore, the loaded titanium composite powder is prepared by the following steps: The magnesium chloride / silicon dioxide composite powder is mixed with n-hexane and titanium tetrachloride in a reaction kettle, stirred at 45-55° C. for 3-4 hours, and the precipitate is collected by centrifugation. The loaded titanium composite powder is obtained after washing and drying.
[0016] The dosage ratio of magnesium chloride / silicon dioxide composite powder, n-hexane and titanium tetrachloride is 30-40g: 600-700mL: 20-30mL.
[0017] Further, the magnesium chloride / silicon dioxide composite powder is prepared by the following steps: The graphene dispersion and the silicon dioxide dispersion are stirred at 35-45° C. for 3-4 hours, filtered to obtain a precipitate, washed and dried to obtain a magnesium chloride / silicon dioxide composite powder; the amount ratio of the graphene dispersion and the silicon dioxide dispersion is 400-500 mL:700-800 mL. Further, the graphene dispersion is obtained by stirring and mixing magnesium chloride graphene, cage-shaped polysilsesquioxane and tetrahydrofuran in an amount ratio of 10-12 g:14-16 g:400-500 mL.
[0018] The silicon dioxide dispersion is obtained by stirring and mixing silicon dioxide powder, 1,4-butanediol and tetrahydrofuran in a dosage ratio of 25-30 g: 12-15 mL: 700-800 mL.
[0019] Further, magnesium chloride graphene is prepared by the following steps: The graphene oxide nanosheets are dispersed in a 1M methylmagnesium chloride tetrahydrofuran solution, ultrasonically treated for 2-3 hours, and the precipitate is collected by centrifugation, washed, and vacuum dried to obtain magnesium chloride graphene.
[0020] Furthermore, the usage ratio of graphene oxide nanosheets and methylmagnesium chloride tetrahydrofuran solution is 10-12 g: 400-500 mL.
[0021] Furthermore, in step 2, the usage ratio of the modified composite powder and the high-density polyethylene is 30-40g:195-225g.
[0022] Furthermore, a method for preparing a polyethylene separator with a high residual bonding rate comprises the following steps: The raw materials are co-extruded into three layers in an extruder for film blowing according to the formula and dosage ratio of the surface layer, the middle layer and the bottom layer. The extrusion film blowing temperature is 180-190°C to obtain a base film of the isolation film. The raw materials are mixed evenly according to the formula and dosage ratio of the coating layer. The coating is applied on the bottom layer of the base film of the isolation film by a coating machine. The coating is 40-50μm thick. The coating is dried and cross-linked and cured at 120-130°C to obtain a polyethylene isolation film with a high residual bonding rate.
[0023] The filling masterbatch is a PE carrier filled with 10-20% inorganic powder, and the inorganic powder includes but is not limited to calcium carbonate and sodium sulfate.
[0024] Beneficial effects of the present invention: (1) The high residual bonding rate polyethylene isolation film prepared by the present invention is obtained by modifying high-density polyethylene with modified composite powder, so that the isolation film has good high temperature resistance and UV resistance. A silicon-philic and heat-shrinkage-resistant isolation film base film is obtained by a three-layer composite method. The isolation film coated with water-based silicone oil has a high residual bonding rate and better performance than the isolation film coated by a solvent method, and the desiliconization rate is greatly reduced.
[0025] (2) The preparation method of the present invention grafts magnesium chloride on the surface of graphene oxide and crystallizes it on the surface of silicon dioxide, thereby compounding magnesium chloride graphene on the surface of silicon dioxide and reducing the agglomeration of silicon dioxide; the crystallized magnesium chloride has an anchoring effect on titanium tetrachloride, so that titanium tetrachloride is grafted and fixed on the crystallized magnesium chloride; titanium tetrachloride and benzyl alcohol interact in a benzene medium to cause a titanium halide reaction, and titanium tetrachloride is oxidized to form titanium oxide particles, thereby improving the ultraviolet resistance of the titanium oxide-loaded composite powder; the modified composite powder has high bonding strength and good dispersibility in high-density polyethylene, and also has an effect of improving the mechanical properties of high residual bonding rate polyethylene isolation membranes. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1: A method for preparing a polyethylene separator with a high residual bonding rate, comprising the following steps: S1. Disperse 10 g of graphene oxide nanosheets in 400 mL of 1 M methylmagnesium chloride tetrahydrofuran solution, ultrasonicate for 2 h, collect the precipitate by centrifugation, wash the precipitate with tetrahydrofuran, and dry it under vacuum at 60° C. to obtain magnesium chloride graphene.
[0028] S2. In a reaction kettle, 10 g of magnesium chloride graphene and 14 g of cage-shaped polysilsesquioxane were stirred in 400 mL of tetrahydrofuran at 55 ° C for 3 h to obtain a graphene dispersion. 25 g of silica powder, 12 mL of 1,4-butanediol and 700 mL of tetrahydrofuran were stirred at 35 ° C for 3 h to obtain a silica dispersion. Then 400 mL of graphene dispersion and 700 mL of silica dispersion were stirred at 35 ° C for 3 h, filtered to obtain a precipitate, washed with n-hexane and dried at 40 ° C for 3 h to obtain a magnesium chloride / silicon dioxide composite powder.
[0029] S3. In a reaction kettle, 30 g of magnesium chloride / silicon dioxide composite powder was mixed with 600 mL of n-hexane and 20 mL of titanium tetrachloride, stirred at 45° C. for 3 h, the precipitate was collected by centrifugation, the precipitate was washed with n-hexane, and dried at 40° C. for 3 h to obtain a loaded titanium composite powder.
[0030] S4. Disperse 30 g of the loaded titanium composite powder in 300 mL of n-decane in a reactor, dissolve 6 mL of benzyl alcohol in 35 mL of benzene, add the mixture into the reactor, reflux at 35°C for 4 h, remove the benzene solvent by rotary evaporation, reflux at 170°C for 8 h, collect the precipitate by centrifugation after cooling, wash the precipitate with chloroform, and dry in vacuo at 70°C to obtain the titanium oxide loaded composite powder.
[0031] S5. Ultrasonic disperse 30 g of titanium oxide-loaded composite powder in 500 mL of anhydrous ethanol in a reactor, add 8 mL of KH550, stir and react for 20 h, collect the precipitate by centrifugation, wash the precipitate with ethanol and deionized water, and vacuum dry at 60° C. for 10 h to obtain a modified composite powder.
[0032] S6. Mix 30g of modified composite powder with 195g of high-density polyethylene at 180°C and 50rpm in a twin-screw extruder for 10min to obtain modified high-density polyethylene. Then mix 65g of modified high-density polyethylene, 5g of linear low-density polyethylene and 20g of maleic anhydride grafted polyethylene to obtain the surface layer raw material; mix 65g of modified high-density polyethylene, 10g of filler masterbatch and 2g of masterbatch to obtain the middle layer raw material; mix 65g of modified high-density polyethylene, 5g of linear low-density polyethylene and 10g of filler masterbatch to obtain the bottom layer raw material. The surface layer raw material, the middle layer raw material and the bottom layer raw material are co-extruded in an extruder for three-layer film blowing, and the extrusion film blowing temperature is 180°C to obtain the isolation film base film. Mix 90g of silicone oil, 4g of cross-linking agent, 5g of curing agent and 0.3g of catalyst evenly to obtain the coating layer raw material. The coating layer raw material is coated on the bottom layer of the isolation film base film by a coating machine, the coating thickness is 40 μm, and it is dried and cross-linked and cured at 120° C. to obtain a polyethylene isolation film with a high residual bonding rate.
[0033] Embodiment 2: A method for preparing a polyethylene separator with a high residual bonding rate, comprising the following steps: S1. Disperse 11 g of graphene oxide nanosheets in 450 mL of 1 M methylmagnesium chloride tetrahydrofuran solution, ultrasonicate for 2.5 h, collect the precipitate by centrifugation, wash the precipitate with tetrahydrofuran, and dry it in vacuum at 65° C. to obtain magnesium chloride graphene.
[0034] S2. In a reaction kettle, 11 g of magnesium chloride graphene and 15 g of cage-shaped polysilsesquioxane were stirred in 450 mL of tetrahydrofuran at 60 ° C for 3.5 h to obtain a graphene dispersion. 27.5 g of silica powder, 13.5 mL of 1,4-butanediol and 750 mL of tetrahydrofuran were stirred at 40 ° C for 3.5 h to obtain a silica dispersion. 450 mL of graphene dispersion and 750 mL of silica dispersion were stirred at 40 ° C for 3.5 h, filtered to obtain a precipitate, washed with n-hexane and dried at 45 ° C for 3.5 h to obtain a magnesium chloride / silicon dioxide composite powder.
[0035] S3. In a reaction kettle, 35 g of magnesium chloride / silicon dioxide composite powder was mixed with 650 mL of n-hexane and 25 mL of titanium tetrachloride, stirred at 50° C. for 3.5 h, the precipitate was collected by centrifugation, the precipitate was washed with n-hexane, and dried at 45° C. for 3.5 h to obtain a loaded titanium composite powder.
[0036] S4. Disperse 35 g of the loaded titanium composite powder in 350 mL of n-decane in a reactor, dissolve 7 mL of benzyl alcohol in 37.5 mL of benzene, add the mixture into the reactor, reflux at 40°C for 4.5 h, remove the benzene solvent by rotary evaporation, reflux at 175°C for 8.5 h, collect the precipitate by centrifugation after cooling, wash the precipitate with chloroform, and dry in vacuo at 75°C to obtain the titanium oxide loaded composite powder.
[0037] S5. Ultrasonic disperse 35 g of titanium oxide-loaded composite powder in 600 mL of anhydrous ethanol in a reactor, add 9 mL of KH550, stir and react for 22 h, collect the precipitate by centrifugation, wash the precipitate with ethanol and deionized water, and vacuum dry at 65° C. for 11 h to obtain a modified composite powder.
[0038] S6. In a twin-screw extruder, 35g of the modified composite powder was mixed with 210g of high-density polyethylene at 185°C and 55rpm for 11min to obtain a modified high-density polyethylene. Then 70g of the modified high-density polyethylene, 6.5g of linear low-density polyethylene and 22.5g of maleic anhydride grafted polyethylene were mixed to obtain the surface layer raw material; 70g of the modified high-density polyethylene, 11g of filler masterbatch and 2.5g of masterbatch were mixed to obtain the middle layer raw material; 70g of the modified high-density polyethylene, 6.5g of linear low-density polyethylene and 11g of filler masterbatch were mixed to obtain the bottom layer raw material. The surface layer raw material, the middle layer raw material and the bottom layer raw material were co-extruded and blown in three layers in an extruder at an extrusion blowing temperature of 185°C to obtain a base film for an isolation film. 91g of silicone oil, 4.5g of a crosslinking agent, 5.5g of a curing agent and 0.35g of a catalyst were mixed evenly to obtain a coating layer raw material. The coating layer raw material is coated on the bottom layer of the isolation film base film by a coating machine, the coating thickness is 45 μm, and it is dried and cross-linked and cured at 125° C. to obtain a polyethylene isolation film with a high residual bonding rate.
[0039] Embodiment 3: A method for preparing a polyethylene separator with a high residual bonding rate, comprising the following steps: S1. Disperse 12 g of graphene oxide nanosheets in 500 mL of 1 M methylmagnesium chloride tetrahydrofuran solution, ultrasonicate for 3 h, collect the precipitate by centrifugation, wash the precipitate with tetrahydrofuran, and dry it in vacuum at 70° C. to obtain magnesium chloride graphene.
[0040] S2. In a reaction kettle, 12 g of magnesium chloride graphene and 16 g of cage-shaped polysilsesquioxane were stirred in 500 mL of tetrahydrofuran at 65 ° C for 4 h to obtain a graphene dispersion. 30 g of silica powder, 15 mL of 1,4-butanediol and 800 mL of tetrahydrofuran were stirred at 45 ° C for 4 h to obtain a silica dispersion. 500 mL of graphene dispersion and 800 mL of silica dispersion were stirred at 45 ° C for 4 h, filtered to obtain a precipitate, washed with n-hexane and dried at 50 ° C for 4 h to obtain a magnesium chloride / silicon dioxide composite powder.
[0041] S3. In a reaction kettle, 40 g of magnesium chloride / silicon dioxide composite powder was mixed with 700 mL of n-hexane and 30 mL of titanium tetrachloride, stirred at 55° C. for 4 h, the precipitate was collected by centrifugation, the precipitate was washed with n-hexane, and dried at 50° C. for 4 h to obtain a loaded titanium composite powder.
[0042] S4. Disperse 40 g of the loaded titanium composite powder in 400 mL of n-decane in a reactor, dissolve 8 mL of benzyl alcohol in 40 mL of benzene, add the mixture into the reactor, reflux and heat at 45°C for 5 h, remove the benzene solvent by rotary evaporation, reflux at 180°C for 9 h, collect the precipitate by centrifugation after cooling, wash the precipitate with chloroform, and dry in vacuo at 80°C to obtain the titanium oxide loaded composite powder.
[0043] S5. Ultrasonic disperse 40 g of titanium oxide-loaded composite powder in 700 mL of anhydrous ethanol in a reactor, add 10 mL of KH550, stir and react for 24 h, collect the precipitate by centrifugation, wash the precipitate with ethanol and deionized water, and vacuum dry at 70° C. for 12 h to obtain a modified composite powder.
[0044] S6. In a twin-screw extruder, 40 g of the modified composite powder and 225 g of high-density polyethylene were mixed at 190° C. and 60 rpm for 12 min to obtain modified high-density polyethylene. Then, 75g of modified high-density polyethylene, 8g of linear low-density polyethylene and 25g of maleic anhydride grafted polyethylene are mixed to obtain the surface layer raw material; 75g of modified high-density polyethylene, 12g of filler masterbatch and 3g of color masterbatch are mixed to obtain the middle layer raw material; 75g of modified high-density polyethylene, 8g of linear low-density polyethylene and 12g of filler masterbatch are obtained to obtain the bottom layer raw material; the surface layer raw material, the middle layer raw material and the bottom layer raw material are co-extruded and blown in an extruder in three layers; the extrusion blowing temperature is 190°C to obtain the isolation film base film; 92g of silicone oil, 5g of cross-linking agent, 6g of curing agent and 0.4g of catalyst are mixed evenly to obtain the coating layer raw material; the coating layer raw material is coated on the bottom layer of the isolation film base film by a coating machine; the coating film thickness is 50μm; the coating film is dried, cross-linked and cured at 130°C to obtain a polyethylene isolation film with a high residual bonding rate.
[0045] Principle of the invention: The invention discloses a method for preparing a titanium-loaded composite powder by grafting magnesium chloride on the surface of graphene oxide, utilizing magnesium chloride to crystallize on the surface of silicon dioxide under the promotion of crystallization by cage-shaped polysilsesquioxane, and compounding magnesium chloride graphene on the surface of silicon dioxide, thereby reducing the agglomeration of silicon dioxide and combining magnesium chloride graphene on the surface of silicon dioxide through cage-shaped polysilsesquioxane. Crystallized magnesium chloride has an anchoring effect on titanium tetrachloride, so that titanium tetrachloride is grafted and fixed on the crystallized magnesium chloride, and titanium-loaded composite powder is obtained. Titanium tetrachloride is oxidized to form titanium oxide particles by interacting titanium tetrachloride with benzyl alcohol in a benzene medium, and titanium halide reaction occurs. Titanium chloride is grafted and loaded on the surface of magnesium chloride, and titanium oxide is loaded on magnesium chloride, thereby improving the anti-ultraviolet ability of the titanium oxide loaded composite powder. The titanium-loaded powder improves its compatibility with polyethylene under the modification of silane coupling agent. Finally, the modified composite powder containing graphene oxide is mixed with high-density polyethylene to obtain modified high-density polyethylene with good dispersion. The high-density polyethylene containing graphene oxide has good high temperature resistance. At the same time, the high titanium dioxide in the modified composite powder has an improvement effect on the anti-ultraviolet ability of the modified high-density polyethylene. The modified composite powder has high bonding strength and good dispersibility in high-density polyethylene, and also has an improvement effect on the mechanical properties of high residual bonding rate polyethylene isolation film. A silicon-philic and heat-shrinkage-resistant isolation film base film is obtained by a three-layer composite method. The isolation film coated with water-based silicone oil has a high residual bonding rate, and its performance is better than that of the isolation film coated by the solvent method, and the desiliconization rate is greatly reduced.
[0046] Comparative Example 1: The difference from Example 1 is that in S2, magnesium chloride graphene is replaced by graphene oxide nanosheets to prepare a polyethylene isolation film with a high residual bonding rate.
[0047] Comparative Example 2: The difference from Example 1 is that in S3, titanium tetrachloride is replaced by nano-titanium dioxide with the same amount of titanium substance, and S4 is not performed to obtain a polyethylene isolation film with a high residual bonding rate.
[0048] Comparative Example 3: The difference from Example 1 is that in S5, 0.18 mol of nano titanium dioxide (the same amount of titanium substance as titanium tetrachloride in S3) and 10 g of graphene oxide nanosheets are used to replace the titanium oxide-loaded composite powder to prepare a polyethylene isolation film with a high residual bonding rate.
[0049] The sources of some reagents in the embodiments and comparative examples are as follows: Cage polysilsesquioxane was purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0050] The silicon dioxide powder is micron silicon dioxide with a particle size of 10-50 μm, purchased from Hebei Ruihuang Metal Materials Co., Ltd.
[0051] Graphene oxide nanosheets, with a diameter of 500 nm and a thickness of 0.8-1.2 nm, were purchased from Suzhou Beike Nanotechnology Co., Ltd.
[0052] The performance tests were conducted on the high residual bonding rate polyethylene isolation films prepared in Examples 1 to 3 and Comparative Examples 1 to 3. The mechanical properties of the materials were tested using an electronic universal testing machine. The high temperature resistance of the materials was tested using a heat deformation Vicat softening point testing machine, where the heating rate was 100°C / h. The desiliconization rate was tested using the Wacker test method. Nitto 31B tape was applied to the high residual bonding rate polyethylene isolation film with a pressure roller and 20 g / cm 2 The standard stainless steel strip was placed in a 70℃ oven for 20 hours, taken out and placed at room temperature for 1 hour, and the test sample was cut out. At the same time, Nitto31B tape was applied to the Teflon film with a pressure roller and 20g / cm 2 The standard stainless steel strips were placed in a 70℃ oven for 20h. After being taken out, they were placed at room temperature for 1h. The blank samples were cut and peeled off from the isolation film and Teflon film respectively. The release force was tested. The desiliconization rate was calculated according to the formula SC=[1-(release force of test sample / release force of blank sample)]x100%. The desiliconization rate of the test sample and the blank sample was tested again after aging with ultraviolet light for 100h. The wavelength of ultraviolet light was 340nm and the irradiance was 0.4W / m 2 / nm.
[0053] The results are shown in Table 1: Table 1: Performance test results of high residual bonding rate polyethylene isolation film project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength (Mpa) 18.6 18.8 18.9 17.7 16.1 14.6 Heat deformation temperature (℃) 81 81 82 75 71 62 Desiliconization rate (%) 7.4 7.1 6.9 7.7 8.5 9.4 Desiliconization rate after UV aging treatment (%) 10.8 10.4 10.2 13.6 14.7 17.3 It can be seen from Table 1 that the high residual bonding rate polyethylene isolation film prepared in the present invention has good tensile strength and high heat deformation temperature, indicating that the isolation film prepared in the present invention has good mechanical properties and high temperature resistance, and the desiliconization rate is low, indicating that the residual grafting rate of the present invention is high, and the desiliconization rate is improved slightly after UV aging treatment, indicating that the UV light resistance is good.
[0054] Since Comparative Example 1 does not contain magnesium chloride, the bonding rate of titanium tetrachloride on graphene oxide nanosheets and silicon dioxide is low, the titanium content of the obtained loaded titanium composite powder is low, and the UV resistance of the prepared polyethylene isolation film is lower than that of Examples 1-3.
[0055] In Comparative Example 2, since nano-titanium dioxide is used to replace titanium tetrachloride, the bonding strength between nano-titanium dioxide and silicon dioxide and graphene oxide nanosheets is low and easy to fall off. Nano-titanium dioxide is easy to agglomerate, which affects the mechanical properties and heat resistance of the prepared polyethylene isolation film, and the improvement in anti-ultraviolet performance is small.
[0056] In Comparative Example 3, only titanium dioxide and graphene oxide nanosheets are modified with a silane coupling agent and then mixed with high-density polyethylene. It does not contain silicon dioxide, and the grafting rate with the silane coupling agent is low. The dispersibility of titanium dioxide in polyethylene is low, and it is not composited with graphene, and the synergistic effect with the graphene nanosheets is low. The resulting polyethylene isolation film has poor UV resistance and low high temperature resistance.
[0057] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polyethylene separator with a high residual bonding rate, comprising a surface layer, an intermediate layer, a bottom layer and a coating layer, characterized in that: The surface layer formula comprises the following raw material components by weight: 65-75 parts of modified high-density polyethylene, 5-8 parts of linear low-density polyethylene and 20-25 parts of maleic anhydride grafted polyethylene; The intermediate layer formula comprises the following raw material components: 65-75 parts of modified high-density polyethylene, 10-12 parts of filler masterbatch and 2-3 parts of color masterbatch; The bottom layer formula comprises the following raw material components: 65-75 parts of modified high-density polyethylene, 5-8 parts of linear low-density polyethylene and 10-12 parts of filler masterbatch; The modified high-density polyethylene is prepared by the following steps: Step 1: Disperse the loaded titanium composite powder in n-decane in a reaction kettle, dissolve benzyl alcohol in benzene, add the mixture into the reaction kettle, reflux and heat at 35-45° C. for 4-5 hours, remove the benzene solvent by rotary evaporation, reflux at 170-180° C. for 8-9 hours, collect the precipitate by centrifugation, wash and vacuum dry to obtain the titanium oxide loaded composite powder; Step 2: In a reaction kettle, the titanium oxide-loaded composite powder is modified with KH550 in ethanol to obtain a modified composite powder, and the modified composite powder is mixed with high-density polyethylene in a twin-screw extruder at 180-190° C. and 50-60 rpm for 10-12 minutes to obtain a modified high-density polyethylene.
2. The high residual bonding rate polyethylene separator according to claim 1, characterized in that: The coating layer formula comprises the following raw material components by weight: 90-92 parts of silicone oil, 4-5 parts of cross-linking agent, 5-6 parts of curing agent and 0.3-0.4 parts of catalyst.
3. The high residual bonding rate polyethylene separator according to claim 1, characterized in that: The amount ratio of the loaded titanium composite powder, n-decane, benzyl alcohol and benzene in step 1 is 30-40 g: 300-400 mL: 6-8 mL: 35-40 mL.
4. The high residual bonding rate polyethylene separator according to claim 3, characterized in that: The loaded titanium composite powder is prepared by the following steps: Mixing magnesium chloride / silicon dioxide composite powder with n-hexane and titanium tetrachloride in a reaction kettle, stirring at 45-55° C. for 3-4 hours, collecting the precipitate by centrifugation, washing and drying to obtain a loaded titanium composite powder; The usage ratio of the magnesium chloride / silicon dioxide composite powder, n-hexane and titanium tetrachloride is 30-40 g: 600-700 mL: 20-30 mL.
5. The high residual bonding rate polyethylene separator according to claim 4, characterized in that: The magnesium chloride / silicon dioxide composite powder is prepared by the following steps: The graphene dispersion and the silicon dioxide dispersion are stirred at 35-45° C. for 3-4 hours, filtered to obtain a precipitate, and washed and dried to obtain a magnesium chloride / silicon dioxide composite powder; the amount ratio of the graphene dispersion and the silicon dioxide dispersion is 400-500 mL:700-800 mL.
6. The high residual bonding rate polyethylene separator according to claim 5, characterized in that: The graphene dispersion is obtained by stirring and mixing magnesium chloride graphene, cage-shaped polysilsesquioxane and tetrahydrofuran in a dosage ratio of 10-12 g: 14-16 g: 400-500 mL; The silicon dioxide dispersion is obtained by stirring and mixing silicon dioxide powder, 1,4-butanediol and tetrahydrofuran in a dosage ratio of 25-30 g: 12-15 mL: 700-800 mL.
7. The high residual bonding rate polyethylene separator according to claim 6, characterized in that: The magnesium chloride graphene is prepared by the following steps: The graphene oxide nanosheets are dispersed in a 1M methylmagnesium chloride tetrahydrofuran solution, ultrasonically treated for 2-3 hours, and the precipitate is collected by centrifugation, washed, and vacuum dried to obtain magnesium chloride graphene.
8. The high residual bonding rate polyethylene separator according to claim 7, characterized in that: The usage ratio of the graphene oxide nanosheets and the methylmagnesium chloride tetrahydrofuran solution is 10-12 g: 400-500 mL.
9. The high residual bonding rate polyethylene separator according to claim 1, characterized in that: The usage ratio of the modified composite powder and high-density polyethylene in step 2 is 30-40g:195-225g.
10. The method for preparing a polyethylene separator with a high residual bonding rate according to claim 1, characterized in that: The preparation method comprises the following steps: The raw materials are co-extruded into three layers in an extruder for film blowing according to the formula and dosage ratio of the surface layer, the middle layer and the bottom layer. The extrusion film blowing temperature is 180-190°C to obtain a base film of the isolation film. The raw materials are mixed evenly according to the formula and dosage ratio of the coating layer. The coating is applied on the bottom layer of the base film of the isolation film by a coating machine. The coating is 40-50μm thick. The coating is dried and cross-linked and cured at 120-130°C to obtain a polyethylene isolation film with a high residual bonding rate.
Citation Information
Patent Citations
Preparation method of high-temperature-resistant modified polyethylene isolating membrane
CN117510916A
Polyethylene / montmorillonoid-supported titanium dioxide composite material and preparation method thereof
CN106633299A
Supported polyolefin catalyst and preparation method thereof
CN113583159A
Nano-modified high-density polyethylene corrugated pipe
CN113603955A
High-heat-resistant shrinkage polyethylene film and preparation method thereof
CN114953681A
Cited By
High-weather-resistance PE film for waterproof coiled material and preparation method of high-weather-resistance PE film
CN120005257A